Cost/effectiveness study of ranibizumab versus bevacizumab in garcia de Orta hospital. Issue 2 (12th March 2012) - Alcobia, A.; Almeida, P. Tavares; Teixeira, A.
Abstract : Background: Age-related macular degeneration (AMD) is one of the main causes of blindness over the age of 50 in developed Western countries. Angiogenic growth factors, particularly vascular endothelial growth factor (VEGF), have a key role in macular degeneration. Therapies that inhibit active forms of VEGF have been shown to be effective in the treatment of wet AMD. Both ranibizumab and bevacizumab inhibit active forms of VEGF although the latter has an off-label use. Purpose: The aim of this study was to compare the use of ranibizumab versus bevacizumab in the treatment of wet AMD in two groups of patients in Garcia de Orta hospital. Materials and methods: This retrospective study, which included 29 patients treated with a 0.05 mg intravitreal injection of ranibizumab and 9 patients treated with 1.25 mg of bevacizumab, was performed from January 2009 to August 2011. Patients were first treated monthly, during the three first months, and then whenever necessary. The number of treatments, visual acuity (Snellen scale), retina thickness and associated costs were compared. Results: Patient ages were 78.2±6.9 and 76±7.5 years, the number of administrations was 3.2±1.7 and 2.9±1.2, the improvement of visual acuity was 0.05±0.11 and 0.06±0.4, the decrease of retina thickness was 80.6±118.4 mm and 133.6±214.4 mm, the cost of administration was 525.5€ and 9.6€ and the cost per patient was 1681.6 € ±893.4 and 27.8€ ±11.5, for the ranibizumab and bevacizumab groups, respectively. Adverse reactions were not reported. Conclusions: Despite the different sizes of the two groups the study has shown no relevant differences between them, in accordance with the CATT group findings, in all the assessed parameters, except the cost with bevacizumab was 60 times lower.